Building country comforts : wisdom on living a sustainable, back-to-basics life - Inwood, Robert; Bruyere, Christian (New York : Sterling, 2011)
'...focuses on the lives of people who built homes and secondary structures in harmony with their natural surroundings. These intrepid individuals used timeless building techniques that are doable by nonprofessionals, from framing walls and windows, to setting floor joints and building roofs. The stories reveal the successes, mistakes, and even later renovations, as well as the personal dreams of those who experience this back-to-nature process...'--P. [4] of cover.
'This book comprises material from the following Sterling titles: In Harmony with Nature, 1981 by Christian Bruye and Country Comforts, 1976 by Christian Bruye.'--T.p. verso.
Keywords: Sustainable buildings; House construction -- Amateurs' manuals